Pengaruh NPL & BOPO Terhadap ROA Pada Bank Maybank Indonesia Periode 2013-2023 - Dea Armasari; Astuti Kelian; Agus Supriatna (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of Non-Performing Loan (NPL) and Operational Expenses to Operational Income (BOPO) on Return on Assets (ROA) at Maybank Indonesia for the period 2013–2023. A quantitative approach was employed using secondary data obtained from the bank’s annual financial statements. Multiple linear regression and classical assumption tests were used for data analysis. The results indicate that NPL has no significant partial effect on ROA, while BOPO has a significant negative effect on ROA. Simultaneously, NPL and BOPO significantly influence ROA. This study highlights the importance of operational efficiency and credit risk management in improving bank profitability. These findings are expected to serve as a strategic reference for banking management in making decisions regarding cost efficiency and asset quality.